Vanek Šiftar, intelektualni steber Prekmurja 20. stoletja - Hojnik, Janja (Časopis za zgodovino in narodopisje, 2024)
Ivan Vanek Šiftar was one of the central social scientists and humanists of the second half of the 20th century in northeastern Slovenia. Already in his student days, he was intensively involved in discussions about the autonomy of Prekmurje and the status of Prekmurje dialect. With some experience in editing student publications in Ptuj, Vanek Šiftar took over the editorship of Mladi Prekmurec before the Second World War. After matriculation in Ptuj, Vanek Šiftar decided to study law at the Faculty of Law in Ljubljana, which was interrupted midway by the war, and he completed it as a student while working in 1953. Towards the end of the war, he transferred to the Red Army and after the war joined the Union communists, through which he wanted to contribute to the improvement of the standard of living and education of the people of Prekmurje. They elected him several times as a Republican and federal deputy. In parallel with his political activity, Šiftar had a legal career. Even before graduating from the Faculty of Law, he worked as a public prosecutor in various Slovenian districts, where he witnessed communist party interference in the work of the judiciary. After his first term as a federal deputy, he enrolled in doctoral studies at the Faculty of Law in Ljubljana, where he received his doctorate in 1965 on the topic of workers’ self-management. He later explained the latter as a project that was manipulated from the initially planned introduction of works councils, through which workers would participate in the management of companies “as good masters”, but not to provide employment to “the biggest slackers”. Due to his knowledge of labour issues, he was appointed chairman of the trade union commission in Maribor and from there in 1965, after his doctorate, he transferred to the Higher School of Law, which was then in its first years of operation. After the retirement of the first director of the school, Vanek Šiftar became the second director of the Law School with the vision of upgrading the school into a Faculty of Law, for which the Law School achieved the right to scientific activity and thus also the printing of legal books, which until then had been reserved for the Faculty of Law in Ljubljana. He worked in the university space at a time when communist party committees were operating at higher education institutions. Although Vanek Šiftar was a member of the communist party, he strove for the dominance of professionalism at the university, he looked for professional and not party staff and encouraged students to think independently. A special chapter in his life was in the second half of the 1970s, when, as a communist professor, he taught political organization courses at the Maribor department of the Faculty of Theology and hung out with the chaplains in the town’s taverns. In 1981, he became the first full-time law professor elected at the University of Maribor. Due to Šiftar’s Hungarian mobilization during WW2, the communist party committee almost prevented his appointment as an emeritus professor, and only the top faculty of the then-new University of Maribor managed to appoint Vanek Šiftar as the University of Maribor’s first emeritus professor in the field of law in 1983.
Keywords: biografije; biography; Communist Party at the University; Higher Law School in Maribor; historian; intelektualec; intellectual; lawyer; Mladi Prekmurec; pravnik; Prekmurje deputy; prekmurski poslanec; profesor; professor; Šiftar, Vanek; Višja pravna šola; zgodovinar; Zveza komunistov na univerzi